KHITAN WANITA PERSPEKTIF MEDIS DAN HUKUM ISLAM - Ibnu Amin (Jurnal AL-AHKAM, 2022)
The term circumcision is not found in the Quran (both as ibarah al-nash and isyarat al-nash) moreover it means the verse to legalize female circumcision. The verse that is often quoted by some scholars to back up the practice of circumcision is the letter an-Nisa' verse 125, surah: 125 and Ali Imran, verse: 95, namely the recommendation to follow Ibrahim's millah, one of the millahs is circumcision. Medical research concluded that female circumcision is not a medical procedure because its implementation is not based on medical indications and has not proven its benefits to the health of the woman as stated in the consideration of Minister of Health Regulation No. 6/2014 concerning Revocation of Minister of Health Regulation 1636/2010 concerning Female Circumcision. Tracing the history that female circumcision departs from the legacy of the Arab tradition that has lasted a long time and when the arrival of Islam got the legitimacy of the Prophet that female circumcision is a "nobility". The method used in this research is library research with normative doctrinal analysis of female circumcision regulations in Indonesia with the Hadith of the Prophet Muhammad regarding female circumcision with several conclusions; First; The practice of female circumcision carried out by medical personnel in Indonesia only cuts off the tip of the clitoris and is not as dangerous as what other countries do or Western accusations that circumcision is an attempt to harass women, supported by Ali Akbar. when having sex, because the clitoris secrete a foul-smelling smegma and become a stimulant for the emergence of cancer of the testicles and cervix. Second; The legitimacy of the Prophet through the phrase "glory for women" if it is understood from a religious perspective, then circumcision is also a sunnah practice for women, from the second socio-cultural aspect when society views a circumcised woman as good (honorable), Islam allows it in accordance with the rules of ushul “al-‘adaah al-muhkamah” and in practice it must be carried out by medical and professional personnel.